ICU intervention during induction chemotherapy for adult patients with newly diagnosed acute myeloid leukemia. (September 2016) - Hartsock, Bobbi; Lim, Matthew J.; Roth, Christine Garcia; Raptis, Nepheli; Weber, David; Sehgal, Alison; Boyiadzis, Michael; Raptis, Anastasios; Hou, Jing-Zhou; Im, Annie; Dorritie, Kathleen; Marks, Stanley; et al.
Highlights: AML patients with a history of IBD are at a higher risk for developing Strep. viridan septicemia during induction chemotherapy. A History of IBD predisposes AML patients to higher risk for ICU intervention during induction chemotherapy. Positive blood cultures also show a trend towards increasing the risk for ICU intervention during induction chemotherapy for newly diagnosed AML. Abstract: We carried out a retrospective study on newly diagnosed AML patients to identify the risk factors associated with intensive care unit (ICU) intervention. One hundred and twenty consecutive AML patients were included. The median cycle of induction therapy (IT) was 2 (range 1–4). Ten patients (8%) needed ICU intervention during IT. The median time from first IT to ICU transfer was 16 days (range 2–88 days). Three patients required vasopressor/s, three mechanical ventilation, and four both. The cumulative probability for ICU intervention rose progressively with increasing cycles of IT received, from 2.5% during first induction to 27.5% at fourth induction. Age, sex, presentation white cell counts and coagulation profiles, cytogenetics, pre-chemotherapy ventricular ejection fractions, and prior chemoradiation were not risk factors. Univariate analysis identified a history of inflammatory bowel disease (IBD) (p = 0.004) (RR = 5.7; p = 0.03) and positive blood cultures (BC) (p = 0.03) (RR = 3; p = 0.06) as significant risks. Multivariate analysis found a history of IBD as the only significant factor (p = 0.03), while positive BC (p = 0.1) trending towards significance. AML patients with a history of IBD and positive BC are at increased risks for ICU intervention during IT.